2021
DOI: 10.1556/1646.2020.00006
|View full text |Cite
|
Sign up to set email alerts
|

Plasma interleukin-6 levels correlate with survival in patients with bacterial sepsis and septic shock

Abstract: In this study, IL-6 levels were assessed as inflammatory biomarker of bacterial sepsis in patients hospitalized at the ICU of the hospital of Colombia.Materials and methodsProspective study on 62 patients diagnosed with sepsis and septic shock. An ELISA assay was used to test serum levels of IL-6 at admission and 48 h after admission. Variables were analyzed by χ2 test (alfa <0.05). Multivariable Cox regression was used to determine the survival with the statistical program SPSS v23.00.ResultsPatient's medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 40 publications
0
4
0
1
Order By: Relevance
“…Serum levels of IL-6 are well known to be involved in sepsis pathogenesis and take part in the systemic response to infection. 22 In this study, there was no difference in serum level of IL-6 in sepsis cases (mean= 203 pg/ml) compared to control group (mean= 101 pg/ml). In contrary, Song et al, 2019 and Smok et al, 2020 found a significant increase in IL-6 in sepsis patients.…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…Serum levels of IL-6 are well known to be involved in sepsis pathogenesis and take part in the systemic response to infection. 22 In this study, there was no difference in serum level of IL-6 in sepsis cases (mean= 203 pg/ml) compared to control group (mean= 101 pg/ml). In contrary, Song et al, 2019 and Smok et al, 2020 found a significant increase in IL-6 in sepsis patients.…”
Section: Discussioncontrasting
confidence: 50%
“…2021 did not find a significant correlation between serum levels of IL-6 and sepsis outcome in terms of mortality. 22 Takahashi et al, 2016 showed that serum IL-6 levels were significant predictors of 28-day mortality and their prognostic value increased over time up to 7 days. 25 On the contrary, Carta et al, 2016 showed elevated serum IL-6 was associated with non-survivors.…”
Section: Il-6 Mirna 15amentioning
confidence: 99%
“…Damit ist die Kinetik von Interleukin-6 deutlich schneller als beim CRP und PCT, die eine "Response"-Halbwertszeit von 6-8 h bis zum Anstieg aufweisen [30]. Darüber hinaus kann IL-6 zur Prognoseabschätzung genutzt werden [30,31].…”
Section: Merkeunclassified
“…Moreover, the onset of inflammatory response, termination, and transition to the homeostasis after sepsis are ATP demanding processes and require biosynthetic precursors provided by metabolic pathways. While studies have shown that an altered inflammatory response in the acute and prolonged phases of sepsis is tightly connected with impaired immune cells metabolism and unfavorable outcomes, the mechanistic mediators of this misconnection are not completely elucidated yet (5)(6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…The early-onset activation of innate immune cells after infection releases proinflammatory cytokines that further mediate responses in the target tissues and in adaptive immune cells like lymphocytes (3). In this context, proinflammatory cytokines, like IL-1 β and IL-6, seem to exert a primary role in mediating (4) autocrine and paracrine signaling, with reflections on biosynthetic pathways (5)(6)(7)(8)(9). For instance, an increase in IL-6 stimulates the liver synthesis of reactant C-reactive protein (CRP), a pro-and anti-inflammatory effector (10,11).…”
Section: Introductionmentioning
confidence: 99%